Linking naturally and unnaturally spun silks through the forced reeling of Bombyx mori. (1st January 2015) - Mortimer, Beth; Guan, Juan; Holland, Chris; Porter, David; Vollrath, Fritz
Graphical abstract: Abstract: The forced reeling of silkworms offers the potential to produce a spectrum of silk filaments, spun from natural silk dope and subjected to carefully controlled applied processing conditions. Here we demonstrate that the envelope of stress–strain properties for forced reeled silks can encompass both naturally spun cocoon silk and unnaturally processed artificial silk filaments. We use dynamic mechanical thermal analysis (DMTA) to quantify the structural properties of these silks. Using this well-established mechanical spectroscopic technique, we show high variation in the mechanical properties and the associated degree of disordered hydrogen-bonded structures in forced reeled silks. Furthermore, we show that this disorder can be manipulated by a range of processing conditions and even ameliorated under certain parameters, such as annealing under heat and mechanical load. We conclude that the powerful combination of forced reeling silk and DMTA has tied together native/natural and synthetic/unnatural extrusion spinning. The presented techniques therefore have the ability to define the potential of Bombyx -derived proteins for use in fibre-based applications and serve as a roadmap to improve fibre quality via post-processing.